A new criterion for testing hypothesis about the covariance function of the homogeneous and isotropic random field - Troshki, V.B. (Carpathian Mathematical Publications, 2015)
In this paper, we consider a continuous in mean square homogeneous and isotropic Gaussian random field. A criterion for testing hypotheses about the covariance function of such field using estimates for its norm in the space $L_p(\mathbb{T}), p≥ 1$ is constructed.